Factors Affecting Preventive Treatment Outcomes for Patients With Newly Diagnosed Chronic Migraine and Their Compliance With Treatment Recommendations in Chongqing Province, China: An Open-Label Prospective Study With Retrospective Baseline - Yuan, Dongli; Zhang, Yixin; Li, Qin; Lv, Yuhua; Li, Xuelian; Yu, Yichuan; Li, Wangwen; Tan, Ge (Frontiers in Neurology, 2020)
Objective: To investigate the factors affecting the efficacy of first oral prophylaxis in patients with chronic migraine (CM) and to assess patient compliance with their medication regimens. Method: To identify the therapeutic effect of prevention medication in 740 patients with newly diagnosed CM that did not receive any preventive treatments after 4 weeks in an open-label prospective study with retrospective baseline from January 2016 to January 2018, the factors that may affect the outcomes of preventive treatment were analyzed based on the demographic characteristics, migraine characteristics, family history of headache, and history of medication overuse. Moreover, the patients were followed up to evaluate their compliance and side-effects with the medication at 4 weeks and 12 weeks. Results: After 4 weeks of prophylaxis, 94.3% (n=698) of the patients persisted with taking the medicine. The treatment was effective for 61.7% of CM patients (n=431) and ineffective for 38.3% (n=267). The results showed that the effectiveness of the preventive treatment was related to the number of headaches per month, and the effect was better for patients with headaches 15-20 d/month than for those with headaches 26-30 d/month (OR=2.78, 95% CI: 1.26-5.75, P=0.006). After 12 weeks of treatment, only 34.5% (n=255) of the patients persisted with taking the medicine. The most common reason for non-compliance in CM patients is appointment difficulty in headache clinic (31.8%). Conclusion: The effect of CM prophylaxis was related to the frequency of headache. Only 34.5% of the patients continued to take medicine after 12 weeks of treatment, suggesting that patient compliance needs to be enhanced in the prophylaxis of CM. For the Chinese headache society, the best way to increase patient compliance should be treatment at dedicated headache centers timely visits to headache specialists.